Assessment of Bowel Preparation Using Low-Volume Sulphate-Based Preparations in Comparison with Macrogols: A Multicenter, Randomized, Comparative Clinical Study of the 3rd Phase - Evgeny D. Fedorov; Viktor V. Veselov; Sergey V. Kashin; Ekaterina V. Tikhomirova; Alexey V. Veselov; Dmitry V. Zavyalov; Anne Kornowski; Tatyana Gorskaya; Magali Volteau; Thierry Ponchon (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2019)
Oral sulphate solution (OSS: sodium sulphate, potassium sulphate and magnesium sulphate) is a low-volume osmotic agent for cleansing the intestines.Aim: in a multicentre, prospective, randomized, 3rd phase study with two parallel groups, the effectiveness, safety and tolerability of OSS was evaluated in comparison with Macrogol 4000 with electrolytes (a reference preparation for bowel cleansing in Russia) in adult patients who were scheduled for routine diagnostic colonoscopy.Methods. This study was conducted in three Russian research centres during the March–December, 2015 period. Men and women over the age of 18 scheduled to undergo routine diagnostic colonoscopy were randomly assigned either to the OSS group or to the Macrogol group with a fractional use mode before the colonoscopy. The colonoscopy researchers were not aware of which preparation had been taken by the patients. Anonymized video records were centrally analysed by three experts. The primary end point was the proportion of patients with a successful bowel preparation for colonoscopy ≥6 points, as determined by the Boston Bowel Preparation Scale of quality assessment (BBPS scale).Results. 296 patients were randomized in the study (147 patients were treated with OSS, 149 patients received Macrogol); 294 participants were included in the Intention to Treat population (ITT-population), and 274 participants were included in the population of patients who completed the study according to the protocol (Per-Protocol; PP-population) (139 patients received OSS, 135 patients received Macrogol). The proportion of patients with a successful bowel preparation (BBPS ≥6 scores) was high in both groups (OSS [PP-population]: 97.2 % (95 % confidence interval [CI] 89.5–99.3), Macrogol [PP-population]: 97.7 % (95 % CI: 90.7–99.4)). The corrected difference between the groups was -0.5 % (95 % CI: -4.2–3.3), thereby demonstrating “no less effective” of OSS as compared to Macrogol. Compliance with the drug use regime was higher in the OSS group than in the Macrogol group (95.7 % versus 82.3 %, respectively, p-value = 0.0011, ITT-population).The most common symptom reported in patients was nausea (27.9 % in the OSS group and 12.9 % in the Macrogol group). The proportion of patients who developed nausea was significantly higher in the OSS group than in the Macrogol group (25.2 % compared with 10.2 % when taking the first dose of the preparation (p = 0.0008) and 19.7 % compared with 6.8 % when taking the second dose of the preparation (p = 0.0016)). Differences in other symptoms (bloating, abdominal pain or abdominal discomfort) between the groups were not significant, with the severity of symptoms being generally mild. The safety profile of the investigated preparations in patients with inflammatory bowel disease (IBD) in remission did not differ from that in the general patient population.The differences in terms of secondary endpoints were not identified, including BBPS assessment for different sections of the colon, the level of polyp detection, the duration and completeness of colonoscopy, and the investigator’s satisfaction with the procedure. The analysis by subgroups also did not reveal any significant differences.Conclusion. In this study, the “not less effectiveness” of the sulphate solution was demonstrated as compared to Macrogol in a fractional use mode. Both preparations were well tolerated. Despite the higher incidence of nausea in the OSS group, the patients showed significantly higher compliance with the OSS mode as compared to that of Macrogol.This study is registered with the ClinicalTrials.gov Registry of Clinical Trials, No. NCT02321462.